High production of secondary metabolites and biological activities of Cydonia oblonga Mill. pulp fruit callus. (July 2022) - De Bellis, Roberta; Chiarantini, Laura; Potenza, Lucia; Gorassini, Andrea; Verardo, Giancarlo; De Marco, Rossella; Benayada, Leila; Stocchi, Vilberto; Cristina Albertini, Maria; Fraternale, Daniele
Graphical abstract: Highlights: An innovative method was developed to obtain Cydonia oblonga pulp callus culture. Pulp callus extract provides a high quantity of secondary compared to fruit pulp. Pulp callus extract has antioxidant and genoprotective effects. Pulp callus extract inhibits α-glucosidase lipase and α-amylase. Abstract: This study has developed an innovative method for the production of secondary metabolites starting from Cydonia oblonga Mill (quince) pulp callus culture. The qualitative and quantitative content of phenolic and triterpenic acids of quince callus extract were elucidated by GC–MS, GC, and HPLC-DAD-ESI-MSn. The callus extract was rich of 5-O-caffeoylquinic acid (5-CQA), 5-p-coumaroylquinic acid (5-p-CoQA) and maslinic and corosolic acid. Quince callus extract's radical scavenging and antioxidant activity were evaluated by 2, 2-diphenyl-1-picrylhydrazyl, 2, 2, -azino-bis(3-ethylbenzothiazoline-6-sulphonic acid), and Oxygen Radical Absorbance Capacity methods. The genoprotection was evaluated by gel electrophoresis analysis and quantitative Real-Time PCR. In addition to the good antioxidant activity the quince callus extract is a strong inhibitor of α-glucosidase (IC50 of 0.25 ± 0.02 mg dw/mL) and lipase (IC50 of 1.99 ± 0.005 mg dw/mL), but mild inhibitor of α-amylase. Therefore, this work would be significant for the future development of a nutraceutical approach to the management of hyperglycemia and dyslipidemia.